Cartografando o discurso de Jair Bolsonaro acerca da pandemia da Covid-19: entre comunicação, desinformação e negação da cidadania no Brasil - Leal, Maiara Raquel Campos (2024)
This research proposes an analysis of the speeches released by President Jair Bolsonaro about the COVID-19 pandemic, during the year 2020, using his official page on the social network Twitter, which was widely used, as a source of observation and data collection. by the president of the republic during the pandemic period. We carry out a multi-method approach, with the interweaving of methodologies known as netnography (Amaral et al. 2008), content analysis (Bardin, 1977, 2000, 2010) and controversy cartography (Venturini, 2009; Latour, 2012; Lemos, 2013) , seeking to identify the regularities, discrepancies and intensities published by Bolsonaro on the topic, focusing on the concepts of communication, disinformation and citizenship. We collected 498 tweets on the topic during 2020, in which economic issues and misinformation represented the biggest regularities identified in their publications, with emphasis on the billion-dollar figures spent by the federal government to control and combat the virus. The main controversies fomented by the president were related to the misinformation spread about the virus and its forms of treatment, with emphasis on issues involving chloroquine and hydroxychloroquine, in addition to conflicts surrounding state social isolation decrees and the controversy with the STF, highlighting a problematic relationship with such entities. We conclude that Bolsonaro relied heavily on a discourse of authority to foment controversies surrounding the COVID-19 pandemic, driving the denial of citizenship to Brazilians, where necropolitics emerges as a type of public policy, since preserving people's lives was a concern secondary role in the management of the health crisis by the federal government under the responsibility of President Jair Bolsonaro, who preferred to focus almost exclusively on matters involving the economy.